Academics’ experiences of networked professional learning - Tusting, Karin; McCulloch, Sharon; Hamilton, Mary (Proceedings of the International Conference on Networked Learning, 2016)
This paper explores academics’ writing practices, focusing on the importance of digital platforms in their processes of collaborative learning. It draws on interview data from the first phase of a research project working closely with academics across different disciplines and institutions to explore their writing practices. The project is framed within a social practice perspective on literacy, which sees reading and writing as practices developed and maintained through participation in a social context, shaped by aspects of people’s purposes, histories and institutional positionings (Barton & Hamilton, 2000; Barton, 2007). The role of an academic in higher education is diverse, and almost every aspect of this role involves specialised forms of writing and knowledge creation in a very wide range of genres for many different kinds of audiences (Hyland, 2011). Transformations in the social and institutional structuring of higher education in recent years have changed the nature of the writing demands faced by academics. At the same time, information and communications technologies have proliferated in the higher education setting. As the demands of academic life have changed in recent years, so the writing practices have changed too. Learning how to engage with these new kinds of genres and practices goes on throughout academics’ careers, much of it in an informal way, collaborating with other people on particular projects and learning as they go along. The paper outlines characteristics of academics’ ongoing professional learning, demonstrating the importance of collaborations on specific projects in generating learning in relation to intellectual and disciplinary aspects of writing, writing strategies and structures, and using digital platforms. A very wide range of digital platforms have been identified by these academics, enabling new kinds of collaboration across time and space on writing and research; but challenges around online learning are also identified, particularly the dangers of engaging in learning in public, the pressures of ’always-on’-ness, and the different values systems around publishing in different forums.